2009
DOI: 10.1002/ca.20783
|View full text |Cite
|
Sign up to set email alerts
|

The ZMF: Is it a reliable intraoperative guide for the IOF?

Abstract: Intraoperative localization of the inferior orbital fissure (IOF) is necessary when making an osteotomy across the zygomatic bone while performing an orbito-zygomatic craniotomy. The zygomatico-facial foramen (ZMF) may serve as good reference point for locating the IOF. In this study, the position of the ZMF was assessed and its location in relation to the IOF was measured in 78 skulls. The ZMF was present in 83.3% of the skulls and when present, was related to the lateral end of the IOF in all cases. The mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
(16 reference statements)
0
0
0
Order By: Relevance
“…Because the ZFN and the ZTN, which are branches of the zygomatic nerve, are located within the zygomatic bone, it is difficult to determine their courses. Most previous studies investigated numbers and locations of zygomatic foramina in dry skulls by macroscopic observation [ 16 - 25 ]. In the present study, the canal connecting the orbital, temporal, or lateral surfaces of the zygomatic bone was defined as the zygomatic canal on micro-CT images, and the openings of the foramina of the zygomatic canal were defined as ZOF, ZTF, and ZFF respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the ZFN and the ZTN, which are branches of the zygomatic nerve, are located within the zygomatic bone, it is difficult to determine their courses. Most previous studies investigated numbers and locations of zygomatic foramina in dry skulls by macroscopic observation [ 16 - 25 ]. In the present study, the canal connecting the orbital, temporal, or lateral surfaces of the zygomatic bone was defined as the zygomatic canal on micro-CT images, and the openings of the foramina of the zygomatic canal were defined as ZOF, ZTF, and ZFF respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the location of the ZFF, where the ZFN emerges, is considered to be an important area to pay attention to when reflecting a mucoperiosteal flap around the cheek region. Previous studies have mainly reported numbers and locations of zygomatic foramina using dry skulls [16][17][18][19][20][21][22][23][24][25], with some reporting anatomical findings of the ZFN exiting the zygomatic foramen [26]. Recently, there has also been a report that involved observation of the zygomatic canal using micro-computed tomography (CT) analysis of seven cadavers [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation